Improving Guideline Compliance and Documentation Through Auditing Neonatal Resuscitation - Root, Laura; van Zanten, Henriette A.; den Boer, Maria C.; Foglia, Elizabeth E.; Witlox, Ruben S. G. M.; te Pas, Arjan B. (Frontiers in Pediatrics, 2019)
Objective: Evaluate whether weekly audits of neonatal resuscitation using video and physiological parameter recordings improved guideline compliance and documentation in medical records. Study design: Neonatal care providers of the Neonatal Intensive Care Unit (NICU) of Leiden University Medical Center reviewed recordings of neonatal resuscitation during weekly plenary audits since 2014. In an observational pre-post cohort study, we studied a cohort of infants born before and after implementation of weekly audits. Video and physiological parameter recordings of infants needing resuscitation were analyzed. These recordings were compared with the prevailing resuscitation guideline and corresponding documentation in the medical record using a pre-set checklist. Results: A total of 212 infants were included, 42 before and 170 after implementation of weekly audits, with a median (IQR) gestational age of 30 (27-35) weeks vs. 30 (29-33) weeks (p=0.64) and birth weight of 1368 (998-1780) grams vs. 1420 (1097-1871) grams (p=0.67). After weekly audits were implemented, providers complied more often to the guideline (63% vs. 77%; p<0.001). Applying the correct respiratory support based on heart rate and respiration, air conditions (dry vs. humidified air), fraction of inspired oxygen (FiO2), timely start of interventions and evaluation of delivered care improved. Total number of correctly documented items in medical records increased from 39% to 65% (p<0.001). Greatest improvements were achieved in documentation of present providers, mode of respiratory support and details about transport to the NICU. Conclusion: Regular auditing using video and physiological parameter recordings of infants needing resuscitation at birth improved providers’ compliance with resuscitation guideline and documentation in medical records.